Ag‐loaded MgSrFe‐layered double hydroxide/chitosan composite scaffold with enhanced osteogenic and antibacterial property for bone engineering tissue. Issue 2 (17th April 2017) - Cao, Dandan; Xu, Zhengliang; Chen, Yixuan; Ke, Qinfei; Zhang, Changqing; Guo, Yaping
Abstract: Bone tissue engineering scaffolds for the reconstruction of large bone defects should simultaneously promote osteogenic differentiation and avoid postoperative infection. Herein, we develop, for the first time, Ag‐loaded MgSrFe‐layered double hydroxide/chitosan (Ag‐MgSrFe/CS) composite scaffold. This scaffold exhibits three‐dimensional interconnected macroporous structure with a pore size of 100–300 μm. The layered double hydroxide nanoplates in the Ag‐MgSrFe/CS show lateral sizes of 200–400 nm and thicknesses of ∼50 nm, and the Ag nanoparticles with particle sizes of ∼20 nm are uniformly dispersed on the scaffold surfaces. Human bone marrow‐derived mesenchymal stem cells (hBMSCs) present good adhesion, spreading, and proliferation on the Ag‐MgSrFe/CS composite scaffold, suggesting that the Ag and Sr elements in the composite scaffold have no toxicity to hBMSCs. When compared with MgFe/CS composite scaffold, the Ag‐MgSrFe/CS composite scaffold has better osteogenic property. The released Sr 2+ ions from the composite scaffold enhance the alkaline phosphatase activity of hBMSCs, promote the extracellular matrix mineralization, and increase the expression levels of osteogenic‐related RUNX2 and BMP‐2. Moreover, the Ag‐MgSrFe/CS composite scaffold possesses good antibacterial property because the Ag nanoparticles in the composite scaffold effectively prevent biofilm formation against S. aureus . Hence, the Ag‐MgSrFe/CS composite scaffold with excellent osteoinductivity and antibacterial property has a great potential for bone tissue engineering. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 863–873, 2018.